(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of acanthosis nigricans (AN) and to analyze the associations between selected anthropometric indices and AN severity in adults in Hanoi in 2025. Methods: A cross-sectional descriptive study was conducted on 57 adults with AN at the Phuong Mai Commune Health Station, Dong Da District, Hanoi, from January to May 2025. Participants underwent clinical examination, grading of neck AN severity according to the Burke scale, and measurement of anthropometric indices including body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR). Results: The mean age was 34.8 ± 10.7 years and 61.4% were female. Neck involvement was present in 100% of participants, followed by the axilla (70.2%) and the knuckles (29.8%). Burke grades of neck AN were distributed mainly in grade 3 (38.6%) and grade 2 (26.3%), with 24.6% in grade 4. Mean BMI was 27.9 ± 4.1 kg/m²; abdominal obesity by WC was present in 73.7% and WHtR ≥ 0.50 in 78.9%. Neck AN severity correlated positively and significantly with WC (rho = 0.61; p < 0.001), WHtR (rho = 0.59; p < 0.001) and BMI (rho = 0.56; p < 0.001), whereas age was not significantly correlated (p = 0.157). The distribution of neck AN severity differed significantly across BMI, WC and WHtR groups (p < 0.05). Conclusion: The severity of AN correlated positively with BMI, WC and WHtR, with WC and WHtR showing the strongest associations.